An UPLC-MS/MS Method for Routine Quantification of Insulin Degludec in Plasma - Zhang, Yudong; Jiang, Yue; Wang, Ya; Wang, Ling; Han, Weijie; Cheng, Xiaoyi; Deng, Xue; Qin, Chunmeng; Liu, Yan (Current Pharmaceutical Analysis, 2020)
Background: Chromatographic methods for determination of insulin degludec in rabbit plasma by Ultra Performance Liquid Chromatography-Tandem Mass Spectrometry were developed. Methods: Analytes were eluted from Waters ACQUITY UPLC® Peptide BEH C18 (2.1×50mm, 300Å) column with a mobile phase of water containing 0.1% formic acid (A) and acetonitrile containing 0.1% formic acid (B). Quantitation of insulin degludec was performed using 1222.06 > 641.24 m/z on Multiple- Reaction Monitoring (MRM) mode. Results: Good linearity was observed in the concentration range of 500-50000 ng/mL (r >0.99), and the lower limit of quantification was 500ng/mL. The within-run and between-run precision (expressed as relative standard deviation, RSD) of insulin degludec were ≤ 14.16% and ≤ 13.64% respectively, and the accuracy was within 94.37-96.35%. The recovery and matrix effects were both within acceptable limits. Conclusions: This method was successfully applied for the pharmacokinetic study of insulin degludec in rabbit after subcutaneous administration.
Keywords: insulin glargine